Pelembagaan Program Kampung Keluarga Berencana di Kelurahan Karangpucung Kecamatan Purwokerto Selatan Kabupaten Banyumas - Andi Antono; Ngalimun Ngalimun; Sri Weningsih; Darmanto Sahat Satyawan (Universitas Serang Raya, 2021)
The Kampung KB Program is a development program that aims to improve the quality of the population in Indonesia. An important aspect in this program is community empowerment. Development with an empowerment dimension is a development activity that occurs in society which is triggered by the desire to advance and allow economic growth and social cohesiveness. This program is a button up, where the government acts as a facilitator and the community innovates according to the issues and needs that develop in the local community. In Banyumas Regency, the program received serious attention from stakeholders so that this stretch was evident in the slogans of the KB village that are often found in almost every sub-district and village / kelurahan. This research was conducted in Karangpucung Village, South Purwokerto District, by observing community activities related to the Kampung KB Program in conducting program socialization and collaboration with other parties, such as sub-district and district governments, community leaders, and experts in the population sector. . The results of the research, which was conducted in a descriptive qualitative manner, showed that for enabling links, the PKK officials were assisted by the head of the RT / RW aggressively and voluntarily to socialize by going from house to house to raise awareness of the residents. The material is not only about family planning but also about local productive businesses and entertainment. For functional relations, this program involves the Puskesmas, family planning officers, midwives and also Babinsa who take an active role. The normative link is that the program is run through the main tasks and functions outlined by the BKKN, instructions and guidance from policy makers such as the sub-district head, village head and the head of district PKK supervisors. Meanwhile, related to the dissemination of the KB village program, it uses events that are widely liked by the community such as grand recitation, art competitions (kentongan), socialization of the risks of early marriage for youth groups, and the provision of supporting facilities, namely props for counseling, as well as the availability of libraries in KB villages.